Myeloid PHD2 deficiency accelerates neointima formation via Hif-1α. (September 2022) - Christoph, Marian; Pfluecke, Christian; Mensch, Matthias; Augstein, Antje; Jellinghaus, Stefanie; Ende, Georg; Mierke, Johannes; Franke, Kristin; Wielockx, Ben; Ibrahim, Karim; Poitz, David M.
Abstract: The key players of the hypoxic response are the hypoxia-inducible factors (Hif), whose α-subunits are tightly regulated by Prolyl-4-hydroxylases (PHD), predominantly by PHD2. Monocytes/Macrophages are involved in atherosclerosis but also restenosis and were found at hypoxic and sites of the lesion. Little is known about the role of the myeloid PHD2 in atherosclerosis and neointima formation. The study aimed to investigate the consequences of a myeloid deficiency of PHD2 in the process of neointima formation using an arterial denudation model. LysM-cre mice were crossed with PHD2 fl/fl, PHD2 fl/fl /Hif1α fl/fl and PHD2 fl/fl /Hif2α fl/fl to get myeloid specific knockout of PHD2 and the Hif-α subunits. Denudation of the femoral artery was performed and animals were fed a western type diet afterwards with analysis of neointima formation 5 and 35 days after denudation. Increased neointima formation in myeloid PHD2 knockouts was observed, which was blunted by double-knockout of PHD2 and Hif1α whereas double knockout of PHD2 and Hif-2α showed comparable lesions to the PHD2 knockouts. Macrophage infiltration was comparable to the neointima formation, suggesting a more inflammatory reaction, and was accompanied by increased intimal VEGF-A expression. Collagen-content inversely correlated to the extent of neointima formation suggesting a destabilization of the plaque. This effect might be triggered by macrophage polarization. Therefore, in vitro results showed a distinct expression pattern in differentially polarized macrophages with high expression of Hif-1α, VEGF and MMP-1 in proinflammatory M1 macrophages. In conclusion, the results show that myeloid Hif-1α is involved in neointima hyperplasia. Our in vivo and in vitro data reveal a central role for this transcription factor in driving plaque-vascularization accompanied by matrix-degradation leading to plaque destabilization. Highlights: Myeloid knockout of PHD2 increases neointima formation after denudation. Myeloid PHD2/Hif1α knockout reverses the proatherogenic effect of PHD2. Myeloid PHD2 knockout lead to increased macrophage plaque content. Macrophage content inversely correlates with collagen content. Macrophage polarization modulates Hif-α and target gene expression.